โมเดลความสัมพันธ์เชิงสาเหตุของการเกี่ยวข้องกับสถานการณ์และความไว้วางใจที่มีต่อการตั้งใจเลือกซื้อจากร้านค้าออนไลน์ของผู้บริโภคชาวไทย - ศรีสวัสดิ์, ทิวาวรรณ; มากมี, ภัทราวดี; สุขสว่าง, พูลพงศ์ (Journal of Graduate School of Commerce-Burapha Review, 2016)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนาโมเดลความสัมพันธ์เชิงสาเหตุระหว่างการเกี่ยวข้องกับสถานการณ์ การรับรู้ความเสี่ยง และความไว้วางใจที่ส่งผลต่อการตั้งใจเลือกซื้อจากร้านค้าออนไลน์ของผู้บริโภคชาวไทย และตรวจสอบความสอดคล้องของโมเดลที่พัฒนาขึ้นกับข้อมูลเชิงประจักษ์ กลุ่มตัวอย่าง จำนวน 500 คน ได้มาจากวิธีการสุ่มแบบแบ่งชั้นแบบเป็นสัดส่วน โดยเป็นผู้ที่เคยซื้อสินค้าและใช้บริการจากร้านค้าออนไลน์ชาวไทย อายุ 18 ปีขึ้นไป เครื่องมือวิจัย คือ แบบสอบถามออนไลน์ วิเคราะห์ค่าสถิติพื้นฐานและค่าสัมประสิทธิ์สหสัมพันธ์โดยใช้โปรแกรม SPSS และวิเคราะห์โมเดลความสัมพันธ์เชิงสาเหตุโดยใช้โปรแกรม Mplus ผลการวิจัยปรากฏว่า 1. โมเดลที่พัฒนาขึ้นมีความสอดคล้องกับข้อมูลเชิงประจักษ์อยู่ในเกณฑ์ดี (ค่าไคสแควร์ เท่ากับ 4.85ค่า df เท่ากับ 3 ค่า p เท่ากับ .18 ดัชนี TLI เท่ากับ .99 ดัชนี CFI เท่ากับ 1.00 SRMR เท่ากับ .03 ค่า RMSEA เท่ากับ .03 และ / df เท่ากับ 1.61) 2. โมเดลความสัมพันธ์เชิงสาเหตุระหว่างการเกี่ยวข้องกับสถานการณ์ การรับรู้ความเสี่ยง และความไว้วางใจที่มีต่อการตั้งใจเลือกซื้อจากร้านค้าออนไลน์ของผู้บริโภคชาวไทยอายุ 18 ปีขึ้นไปที่พัฒนาขึ้น แสดงให้เห็นว่า ความไว้วางใจมีอิทธิพลทางตรงต่อการตั้งใจเลือกซื้อจากร้านค้าออนไลน์มากที่สุด ส่วนการเกี่ยวข้องกับสถานการณ์และการรับรู้ความเสี่ยง มีอิทธิพลทางตรงต่อความไว้วางใจ และมีอิทธิพลทางอ้อมต่อการตั้งใจเลือกซื้อจากร้านค้าออนไลน์ สรุปได้ว่า นอกจากความไว้วางใจแล้ว การเกี่ยวข้องกับสถานการณ์และการรับรู้ความเสี่ยงมีอิทธิพลต่อการตั้งใจเลือกซื้อจากร้านค้าออนไลน์ของผู้บริโภคชาวไทย ABSTRACT The purpose of this research was to develop and validate a causal relationship model among situational involvement, risk perception, and trust expectation as they affect intention to buy from an e-tailer of Thai customers. The 500 participants were obtained by Proportional Stratified random sampling. They were older than 18 years and used to purchasing products from an e-tailer. The research instrument was an online questionnaire. Descriptive statistics were generated using SPSS; causal relationship modeling involved the use of Mplus. The results were as follows: The developed model was consistent with empirical data. Goodness of fit statistics were: chi-square test ( ABSTRACT The purpose of this research was to develop and validate a causal relationship model among situational involvement, risk perception, and trust expectation as they affect intention to buy from an e-tailer of Thai customers. The 500 participants were obtained by Proportional Stratified random sampling. They were older than 18 years and used to purchasing products from an e-tailer. The research instrument was an online questionnaire. Descriptive statistics were generated using SPSS; causal relationship modeling involved the use of Mplus. The results were as follows: 1. The developed model was consistent with empirical data. Goodness of fit statistics were: chi-square test ( ) = 4.85, df = 3, p= .18, TLI = .99, CFI = 1.00, SRMR = .03, RMSEA = .03, and relative chi-square ( /df) =1.61. 2. The developed model between situational involvement, trust expectation, and intention to buy from an e-tailer among Thai customers aged older than 18 years indicated that trust expectation had the strongest significant direct effect on intention to buy from an e-tailer, while situational involvement and risk perception had a significant direct effect on trust expectation, and indirect effects on intention to buy from an e-tailer. In conclusion, besides trust expectation, situational involvement and risk perception also influenced the intention to buy from an e-tailer among Thai customers. ( ) = 4.85, df = 3, p= .18, TLI = .99, CFI = 1.00, SRMR = .03, RMSEA = .03, and relative chi-square ( /df) =1.61. 2. The developed model between situational involvement, trust expectation, and intention to buy from an e-tailer among Thai customers aged older than 18 years indicated that trust expectation had the strongest significant direct effect on intention to buy from an e-tailer, while situational involvement and risk perception had a significant direct effect on trust expectation, and indirect effects on intention to buy from an e-tailer. In conclusion, besides trust expectation, situational involvement and risk perception also influenced the intention to buy from an e-tailer among Thai customers.